2021
DOI: 10.1111/ics.12689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of polyelectrolyte‐surfactant interactions on the rheology and wet lubrication performance of conditioning shampoo

Abstract: Objective The purpose of this study is to understand the impact of the cationic polymer merquat on the rheological behavior of the mixed surfactant system of sodium lauryl ether sulfate (SLES) and cocamidopropyl betaine (CapB) as well as the impact of varying formulation conditions on the wet lubrication performance of the SLES‐CapB‐Merquat system. Methods Rotation mechanical Rheometry was used to study the rheological response of the SLES‐CapB‐Merquat systems. Frequency sweeps were conducted to analyze the rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…16,17 In addition to the competition between these interactions, the multicomponent nature of these systemswhich consist of the polyelectrolyte, the surfactant molecules, both cation and anionic salt species, and watergives rise to a number of desirable properties that can be readily tuned. 20−22 Most importantly, phase behavior and self-assembly give rise to rheological properties such as foamability, wettability, and lubrication which are commonly used to engineer the sensorial properties 8 important for consumer applications (i.e., personal care and food products). Despite the key industrial role of this class of materials, there remain significant gaps in the community's knowledge of the fundamental physics governing the phase behavior of polyelectrolyte−surfactant mixtures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In addition to the competition between these interactions, the multicomponent nature of these systemswhich consist of the polyelectrolyte, the surfactant molecules, both cation and anionic salt species, and watergives rise to a number of desirable properties that can be readily tuned. 20−22 Most importantly, phase behavior and self-assembly give rise to rheological properties such as foamability, wettability, and lubrication which are commonly used to engineer the sensorial properties 8 important for consumer applications (i.e., personal care and food products). Despite the key industrial role of this class of materials, there remain significant gaps in the community's knowledge of the fundamental physics governing the phase behavior of polyelectrolyte−surfactant mixtures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Solutions of oppositely charged polyelectrolytes and surfactants have been studied extensively for a variety of applications, including drug encapsulation, personal care products, and food products. These systems are known to exhibit a number of self-assembly or phase behaviors, driven by a complicated interplay of various intermolecular forces, particularly hydrophobic and electrostatic interactions. Hydrophobicity drives the self-assembly of surfactant molecules into micelle structures, , and both hydrophobic and electrostatic interactions can promote the complexation of the polyelectrolytes with the oppositely charged surfactants. , In addition to the competition between these interactions, the multicomponent nature of these systemswhich consist of the polyelectrolyte, the surfactant molecules, both cation and anionic salt species, and watergives rise to a number of desirable properties that can be readily tuned. Most importantly, phase behavior and self-assembly give rise to rheological properties such as foamability, wettability, and lubrication which are commonly used to engineer the sensorial properties important for consumer applications (i.e., personal care and food products). Despite the key industrial role of this class of materials, there remain significant gaps in the community’s knowledge of the fundamental physics governing the phase behavior of polyelectrolyte–surfactant mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Viscosity, which describes the internal friction within a moving uid, is a key physical property of a wide range of products. Understanding the ow behavior is critical for product development in a range of sectors, including the consumer care, [5][6][7][8][9] oil and gas, [10][11][12][13][14] and pharmaceutical industries. [15][16][17] The ability to quickly screen for viscosity is therefore a valuable tool in accelerating the oen laborious, expensive, and time-consuming research and development cycles that companies currently face.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that two-phase systems (2 ) are also obtained when the surfactant concentration is increased from highly diluted surfactant + polyelectrolyte mixtures [ 5 , 6 , 7 , 8 , 9 ]. This phase separation leads to the depletion of colloidal aggregates (solid-like or liquid-like) from the aqueous phase, resulting in their deposition on the solid surface which in turn is fundamental for defining the final performance of the formulations [ 10 , 11 , 12 , 13 ]. Therefore, it is possible to assume that the performance of most of the currently commercialized polyelectrolyte + surfactant formulations is mediated by the appearance of an enhanced deposition as the result of a dilution-induced precipitation process, the so-called Lochhead effect [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%